Pengaruh Tingkat Pengetahuan Terhadap Kepatuhan Pasien Minum Obat Anti Tuberkulosis (OAT) di Puskesmas Kota Pekalongan - Purgiantari, Purgiantari; Suryoputri, Masita Wulandari; Endriastuti, Nialiana Endah (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2022)
Background: Adherence is one of the most critical factors in the success of pulmonary tuberculosis therapy. Non-compliance of patients taking anti-tuberculosis drug results in a high rate of treatment failure, increasing the risk of disease severity and death. Objective: This study aims to investigate the impact of knowledge level on patient compliance in taking anti-tubercular medication. Methods: This observational, cross-sectional study employed a total sampling method. The levels of knowledge and compliance were assessed using a validated questionnaire administered to patients with pulmonary tuberculosis at the Pekalongan City health center (Puskesmas). Results: Among the 52 participants, 44.23% (n=23) demonstrated a high level of knowledge, and 86.5% (n=45) exhibited good compliance. Spearman correlation test analysis revealed a significant influence of knowledge level on patient compliance in taking antituberculosis drugs (p=0.001, r=0.341), indicating that higher knowledge levels correspond to better patient compliance. Conclusion: The study suggests that patient compliance with antitubercular medication improves as knowledge level increases.